CXCL16 regulates renal injury and fibrosis in experimental renal artery stenosis - Ma, Zhiheng (Am J Physiol Heart Circ Physiol, 2016)
Recent studies have shown that inflammation plays a critical role in the initiation and progression of hypertensive kidney disease, including renal artery stenosis. However, the signaling mechanisms underlying the induction of inflammation are poorly understood. We found that CXCL16 was induced in the kidney in a murine model of renal artery stenosis. To determine whether CXCL16 is involved in renal injury and fibrosis, wild-type and CXCL16 knockout mice were subjected to renal artery stenosis induced by placing a cuff on the left renal artery. Wild-type and CXCL16 knockout mice had comparable blood pressure at baseline. Renal artery stenosis caused an increase in blood pressure that was similar between wild-type and CXCL16 knockout mice. CXCL16 knockout mice were protected from RAS-induced renal injury and fibrosis. CXCL16 deficiency suppressed bone marrow-derived fibroblast accumulation and myofibroblast formation in the stenotic kidneys, which was associated with less expression of extracellular matrix proteins. Furthermore, CXCL16 deficiency inhibited infiltration of F4/80(+) macrophages and CD3(+) T cells in the stenotic kidneys compared with those of wild-type mice. Taken together, our results indicate that CXCL16 plays a pivotal role in the pathogenesis of renal artery stenosis-induced renal injury and fibrosis through regulation of bone marrow-derived fibroblast accumulation and macrophage and T-cell infiltration.